The Relationship between Media Use and Body Mass Index among Secondary Students in Kuching South City, Sarawak, Malaysia - Cheah, Whye Lian; Chang, Ching Thon; Rosalia, Saimon; Charles, Lai Dekun; Yii, Sze Lin; Tiong, Pik Hoong; Yeap, Kim Pey (Universiti Sains Malaysia, 2011)
Background: Overweight and obesity rates among adolescents have increased substantially over the years. This study aimed to determine the body mass index (BMI) of students and parents and the relationship among media use, BMI, socio-demographic profiles, and snacking behaviour during television watching of secondary school students in Kuching South City.